Advances in chromatin remodeling and its role in the molecular mechanism of leukemia - Liang-Liang Li (Journal of Hainan Medical University, 2020)
Leukemia is a type of malignant clonal disease of hematopoietic stem cells. Its root cause is the change in the structure and function of genetic material inside hematopoietic stem/progenitor cells. DNA is no longer the only substance that affects heredity. Research on genetic material other than DNA is getting deeper and deeper. Scientists have found that epigenetic abnormality is also an important part of the pathogenesis of leukemia. Epigenetics involves DNA, protein, chromatin and RNA, and they are interrelated and regulated by each other in regulating gene expression. In recent years, chromatin remodeling has become a research focus in the field of oncology epigenetics, and its role in gene expression regulation has been recognized. To explore the potential value of chromatin remodeling in human pathogenesis and therapeutics, this review describes chromatin remodeling and remodeling factor classification, and its impact on human diseases, particularly leukemia.